Spinal angiography in a patient with spinal dural arteriovenous fistula was falsely reported as normal: A Case Report - Tian Jiayu; Jin Haiqiang; Duan Hongzhou; Sun Yongan (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Introduction: Spinal Dural Arteriovenous Fistulae (SDAVF) is a vascular malformation of the spinal cord. Digital Subtraction Angiography (DSA) is the gold standard for the diagnosis. Sometimes there are false negatives. Case Report: The authors describe a 62-year-old male with SDAVF. He presented with a slow ascent of sensory and motor impairments. DSA showed normal at first, but showed the presence of SDAVF in the second time. Conclusion: DSA is needed to diagnose the suspected dural arteriovenous fistula, but it can't be excluded completely if the contrast is negative. If the symptom is typical, DSA can be rechecked as appropriate to further clarify, avoid misdiagnosis and mistreatment as much as possible, and improve the prognosis of the patients.